2009
DOI: 10.4161/cbt.8.17.9203
|View full text |Cite
|
Sign up to set email alerts
|

Ozone ameliorates methotrexate-induced intestinal injury in rats

Abstract: Methotrexate (Mtx) is an effective chemotherapeutic agent used in various cancer treatments. Gastrointestinal toxicity is the drug's major limiting factor, arising mainly from oxidative damage. It has been proposed that ozone (O(3)) is an activator of antioxidant enzymes. Thus, this study was designed to investigate the efficacy of ozone therapy in the prevention of Mtx-induced intestinal injury in rats. Twenty rats were allocated into three groups: sham, Mtx alone (untreated) and Mtx + O(3) (treated with ozon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
41
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 19 publications
6
41
1
2
Order By: Relevance
“…Our results revealed that MTX induced severe morphological intestinal injury and increase in the level of lipid oxidation marker, MDA, and decrease in the levels of the antioxidant markers, GSH and GSH-Px, similarly to previous studies [12,16,25,29]. JHP supplementation ameliorated the MTX-induced morphological intestinal injury and preserved intestinal MDA, GSH and GSH-Px levels.…”
supporting
confidence: 90%
See 3 more Smart Citations
“…Our results revealed that MTX induced severe morphological intestinal injury and increase in the level of lipid oxidation marker, MDA, and decrease in the levels of the antioxidant markers, GSH and GSH-Px, similarly to previous studies [12,16,25,29]. JHP supplementation ameliorated the MTX-induced morphological intestinal injury and preserved intestinal MDA, GSH and GSH-Px levels.…”
supporting
confidence: 90%
“…MTX reportedly causes morphological intestinal injury associated with oxidative damages [12,16,20,29]. Our results revealed that MTX induced severe morphological intestinal injury and increase in the level of lipid oxidation marker, MDA, and decrease in the levels of the antioxidant markers, GSH and GSH-Px, similarly to previous studies [12,16,25,29].…”
supporting
confidence: 89%
See 2 more Smart Citations
“…In order to minimize side-effects of MTX in patients, the studies focused on antioxidants. [28][29][30][31] One of them, GE, was mostly emphasized on its antioxidant properties in a number of in vitro and in vivo studies. 17,32,33 Various studies also presented that GE has been tried in the repair of MTX-induced intestinal injury.…”
Section: Discussionmentioning
confidence: 99%